2011
DOI: 10.1111/j.1463-1326.2011.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimized glycaemic control achieved with add-on basal insulin therapy improves indexes of endothelial damage and regeneration in type 2 diabetic patients with macroangiopathy: a randomized crossover trial comparing detemir versus glargine

Abstract: Optimized glycaemic control by add-on basal insulin improved indexes of endothelial damage and regeneration. Compared to glargine, detemir achieved similar endothelial protection with lower weight gain and less hypoglycaemia. These results might have implications for therapy of aging T2D patients with cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
(45 reference statements)
2
43
0
1
Order By: Relevance
“…Insulin dosage was reduced significantly, but it was not correlated with changes in cEPCs number or PACs adhesion. This is interesting, as insulin has been shown to improve cEPCs number [40, 41] and function in type 2 diabetes [42, 43]. However, the improvement in cEPCs number in Fadini et al [41] could be attributed to improvement in HbA1c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin dosage was reduced significantly, but it was not correlated with changes in cEPCs number or PACs adhesion. This is interesting, as insulin has been shown to improve cEPCs number [40, 41] and function in type 2 diabetes [42, 43]. However, the improvement in cEPCs number in Fadini et al [41] could be attributed to improvement in HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting, as insulin has been shown to improve cEPCs number [40, 41] and function in type 2 diabetes [42, 43]. However, the improvement in cEPCs number in Fadini et al [41] could be attributed to improvement in HbA1c. This is in contrast with Humpert et al [40], who showed that effect of insulin on the cEPCs number is independent of HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…75 Blood pressure lowering with different classes of drugs has shown ability to counteract EPC reduction in hypertensive patients. 102, 103 Blood glucose lowering with insulin therapy in diabetic patients was able to increase circulating CD133+KDR+ and CD34+CD133+KDR+ EPCs, 104 while other anti-diabetic medications may be active on EPCs. 105 LDL-apheresis in patients with familial hypercholesterolemia increased CD34+KDR+ EPCs (although CD34+CD133+KDR+ cells remained unchanged), 106 while statin therapy is among the best characterized intervention to increase EPCs.…”
Section: Epcs As Biomarkers Of Cardiovascular Diseasementioning
confidence: 99%
“…The second set (SET2) was a cohort of diabetic subjects (N = 42) that has been described previously [12]. Patients and controls were recruited at the outpatient clinics of the Division of Metabolic Diseases, University Hospital of Padova, Italy.…”
Section: Patientsmentioning
confidence: 99%